(untitled) (Medical Forum Monthly, 2024)
Objective: This prospective study aims to evaluate the efficacy and safety of the reverse striping technique using a locally available diamond burr, comparing it with conventional surgical methods. Study Design: A Prospective Cohort Study Place and Duration of Study: This study was conducted at the Eye Department of Fazaia Ruth Pfau Medical College, Karachi from November 2022 to November 2023. Methods: After ethics approval and informed consent, patients underwent thorough pre-operative assessments. They randomized to receive either conventional surgery or the reverse striping technique. Post-operative follow-ups conducted to evaluate visual acuity, corneal astigmatism, recurrence rates, and patient satisfaction. Results: The study cohort comprised 15 females (41.6%) and 25 males (58.3%) with a median age of 47.22 years. The mean visual acuity for the entire cohort was 0.62134 LogMAR preoperatively. Postoperative mean visual acuity was 0.4467 LogMAR in Group 3 and 0.795 LogMAR in Group 4, with no significant difference between preoperative and postoperative outcomes. The mean k1 and k2 readings showed a reduction of 1.5D in cylindrical numbers postoperatively. Recurrence rates were 10% (RT1) and 90% (RT0). Conclusion: The reverse striping technique using a locally available diamond burr offers a promising alternative for pterygium surgery, with moderate visual acuity improvements, significant reduction in corneal astigmatism, and a low recurrence rate. Future research should focus on standardizing surgical methods and exploring additional treatments to enhance visual outcomes and further reduce recurrence rates.